Cardiorenal Syndrome in Type 2 Diabetes Mellitus – Rational Use of Sodium–glucose Cotransporter-2 Inhibitors. Issue 2 (2020) - Kalra, Sanjay; Aydin, Hasan; Sahay, Manisha; Ghosh, Sujoy; Ruder, Sundeep; Tiwaskar, Mangesh; Kilov, Gary; Kishor, Kamal; Nair, Tiny; Makkar, Vikas; Unnikrishnan, Ambika Gopalakrishnan; Dhanda, Dinesh; et al.
No abstract available